Computed tomography: the investigation of choice for aortic dissection?. Issue 2 (August 1986) - Singh, H; Fitzgerald, E; Ruttley, M S
Abstract : Computed tomography has become established as complementary to aortography in the investigation of patients with suspected aortic dissection. Two cases of dissecting aneurysm are reported in which extensive aortography failed to show evidence of dissection. In both cases dissection was demonstrated by computed tomography. The diagnosis was confirmed in one case at operation and in the other case by follow up. It is suggested that computed tomography is the diagnostic method of first choice in aortic dissection.